1978
DOI: 10.1128/aac.13.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Evaluation of 5-Episisomicin (Sch 22591), a New Semisynthetic Aminoglycoside

Abstract: 5-episisomicin (Sch 22591) is a novel semisynthetic aminoglycoside with a spectrum and potency similar to gentamicin in its activity against susceptible bacterial strains, but with increased potency against Pseudomonas, Providencia , and Proteus rettgeri . It is also more active than tobramycin and amikacin against these last-mentioned species. Against resistant strains, Sch 22591 is significantly more active than gentamicin or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Although it had the best activity of the agents tested against bacteria resistant by virtue of a permeability barrier, the concentrations could only be achieved in urine and not in blood. The recent studies by Waitz et al (10) indicate that the in vitro observations concerning 5-episisomicin are confirned in protection experiments in animals. However, it appears that 5-episisomicin is not less toxic in the experimental animal.…”
Section: Resultsmentioning
confidence: 99%
“…Although it had the best activity of the agents tested against bacteria resistant by virtue of a permeability barrier, the concentrations could only be achieved in urine and not in blood. The recent studies by Waitz et al (10) indicate that the in vitro observations concerning 5-episisomicin are confirned in protection experiments in animals. However, it appears that 5-episisomicin is not less toxic in the experimental animal.…”
Section: Resultsmentioning
confidence: 99%
“…The plates were slowly thawed at 4°C before inoculation with 5 p,l of 1:100 dilutions of 24-h cultures. The MIC, the lowest drug concentration at which no visible growth was observed, was determined after 24 and 48 h. In addition to gentamicin, tobramycin, amikacin, netilmicin, and dibekacin, aminoglycosides tested included sisomicin (Schering Corp.), 2'-N-ethyl-netilmicin (Schering Corp.), 6'-N-ethyl-netilmicin (Schering Corp.), astromicin (fortimicin; Kyowa Hakko), HAPA-gentamicin B (Sch 21420; Schering Corp. [15]), 5-episisomicin (Sch 22591; Schering Corp. [24]), and apramycin (Eli Lilly & Co.).…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers have carried out similar types of mutant-feeding studies with other aminoglycosides; some years later, workers at Schering-Plough isolated D Ϫ mutants of Micromonospora inyouensis that were blocked in the production of sisomicin and employed medium supplementation with a variety of DOS to produce analogues of this aminoglycoside. This work led to the identification of a compound, 5-episisomicin that had improved antibacterial activity compared to gentamicin and also inhibited certain classes of gentamicin-resistant bacteria; it eventually became the basis of a useful therapeutic agent [14]. We found that 5-episisomicin has very good potency in blocking certain ribozyme-based reactions.…”
Section: Future Prospectsmentioning
confidence: 97%